A VISUAL AND VERBAL ANALYSIS OF CHILDREN'S REPRESENTATION IN TELEVISION ADVERTISEMENT - Ardhernas, Elka Zenereshynta Nuvra (2014)
The study investigates the representation of children in television advertisement of 3 Indie+ cellular phone operator. The method of the study is descriptive qualitative. The aim of the study is to examine the representation of children visually and verbally in the 3 Indie+ cellular phone operator advertisement. Based on the data analysis, the study finds that visually children are represented as a naive person who is "pretending to know" adult life when they are still a child. Children are verbally represented to tell about their hope, obsession, and aspirations in the future. They also tell about their naive imaginations of how an adult life is. The signification of the representation can be understood that unlike other provider, using 3 Indie+ is very easy, it is not as hard as to live as adults. Keywords: Advertisement, cellular phone, representation, semiotic, text, and visual grammar. Penelitian ini mengenai representasi anak-anak dalam iklan televisi (operator telepon selular 3 Indie+). Metode yang digunakan dalam penelitian ini adalah metode deskriptif kualitatif. Tujuan dari penelitian ini adalah untuk mengetahui representasi anak-anak dalam iklan operator telepon selular 3 Indie+ secara visual maupun secara verbal. Berdasarkan analisis data, penelitian ini menunjukkan bahwa secara visual, anak-anak direpresentasikan sebagai orang naif yang "berlagak tahu" tentang kehidupan orang dewasa ketika mereka masih anak-anak. Secara verbal, anak-anak direpresentasikan untuk menyampaikan tentang imajinasi mereka akan kehidupan orang dewasa. Makna dari representasi tersebut dapat dipahami bahwa tidak seperti provider lain, menggunakan 3 Indie+ sangat mudah dan tidak sulit sesulit menjalankan kehidupan sebagai orang dewasa. Kata Kunci: iklan, telepon selular, representasi, semiotika, teks, dan visual grammar